The Relationship between Health Literacy, Illness Perception, and Self-Management Adherence among Hemodialysis Patients in Indonesia - Pratiwi, Sri Hartati; Sari, Eka Afrima; Kurniawan, Titis (Journal of Health and Nutrition Research, 2025)
Hemodialysis patients' self-management is critical for maintaining their quality of life and minimizing complications. Patients' health literacy and perception of the disease are essential for their acceptance of the condition and treatment. However, the relationship between these variables and self-management among hemodialysis patients remains unclear. This study aims to identify the relationship between health literacy, perception of disease, and self-management among hemodialysis patients. This correlational study was cross-sectional design, with 129 hemodialysis patients consecutively recruited from a hemodialysis unit of a tertiary hospital in West Java, Indonesia. Data were collected using the Brief-Illness Perception Questionnaire (Brief-IPQ), the European Health Literacy Survey Questionnaire (HLS-EU-Q47), and the End Stage Renal Disease Adherence Questionnaire (ESRD-AQ). The data were analyzed using Pearson correlation analysis. Most of the patients had sufficient or excellent health literacy (74.4%), negative illness perception (50.4%), and low self-management practices (71.3%). Pearson’s correlation analysis revealed a positive correlation was found between health literacy and self-management practices (r = .189; ρ=0.032). Additionally, there was a negative correlation between illness perception and health literacy (r = -.27; ρ= .002) as well as between illness perception and self-management practices (r = -.762; ρ= .000). Positive illness perception and better self-management practices correlate with a higher level of health literacy. These findings highlight the importance for healthcare staff to facilitate positive illness perceptions and self-management practices, and to consider these factors as vital aspects in developing self-management education programs for ESRD patients.